Decoding Generation Z's Shopping Behaviour: Key Insights for E-Retailers in Today's Digital Landscape - ZEENA PREMILA CUTINHA , DR.S. SRIRANJANI MOKSHAGUNDAM (Cuestiones de Fisioterapia, 2025)
The study investigates the shopping habits of Generation Z consumers at specific online retailers. Understanding the factors that influence their engagement and loyalty is crucial for businesses aiming to effectively target this tech-savvy demographic in the advancement of digital technology and the significance of online shopping. Using a mixed-methods approach, including in-depth interviews and surveys, the research reveals that convenience, cost, product quality, brand reputation, and social media influence are significant drivers of Generation Z's online purchasing behaviour